2020
DOI: 10.2169/internalmedicine.4283-20
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Deep-seated Dentofacial Abscesses Caused by Multidrug-resistant Viridans Group Streptococci

Abstract: Odontogenic infections, generally caused by dental caries and periodontal disease, can result in fatal illness. We herein report a 71-year-old Japanese woman with type 2 diabetes and hemodialysis who suffered from multiple dentofacial abscesses mainly caused by multidrug-resistant Streptococcus oralis. She complained of pain and swelling of her face, with an extraoral fistula from the left cheek. Following 3 surgical debridement procedures and partial mandibulectomy, in addition to 12 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“… 34 The association of S. viridans with post dental procedure IE observed here is consistent with the former being a common cause of odontogenic diseases. 35 These findings suggest that any prophylactic antibiotic use for dental procedures should be tailored to best protect against S. viridans to ensure maximal efficacy. Importantly, while amoxicillin is commonly used for antibiotic prophylaxis prior to dental procedures in at-risk patients, studies have shown S. viridans to be resistant to amoxicillin to differing degrees, and may contribute to the lack of efficacy of prophylactic antibiotics found in some studies.…”
Section: Discussionmentioning
confidence: 99%
“… 34 The association of S. viridans with post dental procedure IE observed here is consistent with the former being a common cause of odontogenic diseases. 35 These findings suggest that any prophylactic antibiotic use for dental procedures should be tailored to best protect against S. viridans to ensure maximal efficacy. Importantly, while amoxicillin is commonly used for antibiotic prophylaxis prior to dental procedures in at-risk patients, studies have shown S. viridans to be resistant to amoxicillin to differing degrees, and may contribute to the lack of efficacy of prophylactic antibiotics found in some studies.…”
Section: Discussionmentioning
confidence: 99%